Fe(II)–Pt(II) based metallo-supramolecular macrocycle nanoarchitectonics for high-performance gel-state electrochromic device. (April 2023) - Halder, Sayan; Chakraborty, Chanchal
Abstract: Herein, a Pt containing Fe-terpyridine-based square-shaped metallo-supramolecular macrocycle was synthesized, utilizing the advantage of Pt(II)-based complex to form the square macrocycles at room temperature. The step-wise synthesized terpyridine-pyridine containing ligand, its Fe(II)-complex, and the Pt–Fe-TpyN macrocycle were fully characterized by different spectroscopic, structural, and morphological characterizations. Incorporating a Pt(II) component can improve the solution processability and the electronic communication between metal centers via conjugated ligands. The solution processable Pt–Fe-TpyN macrocycle was used as an active ECM film to fabricate a gel-state ECD, which demonstrated a reversible purple to transparent dirty white color change during electrochromism with a high optical contrast of 49% in +3/-2 V voltage window utilizing the redox of Fe (II) metal centers. The ECD also showed fast-switching times of 0.58 and 4.4 s for t c and t b, respectively, along with a high coloration efficiency of 227 cm 2 C −1 and cycle stability over 1000 cycles. The EC parameters were unaltered in larger sized devices also. The current work may provide a valuable method for synthesizing metallo-macrocycles with improved solubility and film forming ability by incorporating a Pt(II) component into the structure for spectrochemical and optoelectronic devices. Graphical abstract: Image 1 Highlights: Synthesis of Fe(II)–Pt(II)-based metallo-supramolecular macrocycle. Terpyridine-pyridine containing heteroditopic ligand was used as a linker. Macrocycle shows purple to white electrochromism with fast switching times. Highly durable electrochromism with high optical contrast in solid-state devices.